The Importance of Discipline in Language Teaching - Ramos, Brandon (CIEX JOURNAL, 2021)
Discipline is the practice of making people obey rules or standards of behavior and punishing them when they do not. But it can also be defined as the quality of being able to behave and work in a controlled way which involves obeying rules or standards. Both definitions are based around the same idea, which is to follow the rules. These definitions can be applied anywhere. Our home, school, our jobs, and even our hobbies and activities we do.